Pengaruh Kemudahan Produk Pegadaian Syariah Terhadap Minat Nasabah di Watampone - Arini Putri Astuti; Abd. Hafid; Andi Ika Fahrika (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2024)
This study analyzes the influence of Sharia Pawnshop product ease on customer interest in Watampone. A quantitative research was conducted by distributing questionnaires to 50 respondents who are Sharia Pawnshop customers. Research variables include product ease, comprising service accessibility, simple procedures, compliance with sharia principles, and payment flexibility. Statistical analysis shows a positive and significant influence of product ease on customer interest, with a significance value of 0.000 (< 0.05). The determination coefficient (R Square) of 0.750 or 75% indicates that product ease contributes substantially to customer interest, while 25% is influenced by other factors such as friendly and professional service. The research findings suggest that Sharia Pawnshop product ease significantly affects customer interest in Watampone.